Hubungan Umur dan Pendidikan dengan Pengetahuan Ibu tentang Persiapan Remaja dalam Menghadapi Menarche di Sekolah Dasar Negeri 101752 Klambir V Medan Tahun 2019 - Desriati Sinaga; Enima Hallawa (STIKes Santa Elisabeth Medan, 2020)
Introduction: Teenager or Adolescence is a transition step between childhood and adulthood who will have puberty experience which marked by the arrival of the first menstruation (menarche). The Readiness of young women in facing the menarche requires the supporting of parents, especially mothersMethod: The purpose of this study was to identify the relationship between age and education of mother's knowledge with the preparation of young women in facing of menarche in State Elementary School 101752 Klambir V Medan in 2019.Result: This research used quantitative methods with correlation techniques and data collection techniques were in the form of questionnaires. The respondents in this study were all mothers who had sixth grade teenage girls in State Elementary School 101752 Klambir V Medan in 2019 totaling 43 people. The results showed that the respondents with age> 35 years who have good knowledge were 27 people (81.8%). Respondents with senior high school graduation who have good knowledge were 16 people (72.8%)Duscussion: Conclusion, there is the relationship between age and mother's knowledge about the preparation of young women in facing menarche with a significant value of 0.006. There is no relationship between education and mother's knowledge about the preparation of young women in the face of menarche with a significant value of 0.24.